2018
DOI: 10.1557/jmr.2018.175
|View full text |Cite
|
Sign up to set email alerts
|

Thermally oxidized electron beam melted γ-TiAl: In vitro wear, corrosion, and biocompatibility properties

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Authors such as Caballero et al, Martinez-Villafañe et al, Karlsson et al, Bermingham et al and Casadebaigt et al have studied the oxidation kinetics of the Ti-6Al-4V alloy with EBM processing and wire and arc additive manufacturing (WAAM) [ 33 , 34 , 35 ]. In other studies, the oxidation behavior of titanium aluminides was studied by Terner et al, Som et al and Wang et al [ 36 , 37 , 38 ]. One of the first studies on the oxidation kinetics of a titanium alloy (Ti-5.5Al-3.4Sn-3.0Zr-0.7Mo-0.3Si-0.4Nb-0.35Ta wt.%) manufactured by LBM was published by Zhou et al [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Authors such as Caballero et al, Martinez-Villafañe et al, Karlsson et al, Bermingham et al and Casadebaigt et al have studied the oxidation kinetics of the Ti-6Al-4V alloy with EBM processing and wire and arc additive manufacturing (WAAM) [ 33 , 34 , 35 ]. In other studies, the oxidation behavior of titanium aluminides was studied by Terner et al, Som et al and Wang et al [ 36 , 37 , 38 ]. One of the first studies on the oxidation kinetics of a titanium alloy (Ti-5.5Al-3.4Sn-3.0Zr-0.7Mo-0.3Si-0.4Nb-0.35Ta wt.%) manufactured by LBM was published by Zhou et al [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…So, it is one of the most promising alloy systems for bearings, automobiles and related applications [14]. TiNi-based alloys have also found widespread application in fields such as aerospace engineering, intelligent control, and medical implants [15][16][17]. As with all IMCs, TiNi has good mechanical strength at elevated temperatures; however, it exhibits relatively brittle behavior under ambient temperature conditions, and thus has restricted applicability at lower working temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Cu-based TiAl alloys are a promising solution for high-temperature structural applications with high strength and toughness requirements [ 11 , 12 ]. Moreover, several studies have shown that Cu addition is also beneficial in improving the biocompatibility, corrosion resistance, and ductility of TiAl alloy [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%